Ethics, law and dignity. On Manuel Atienza’s contribution to biolaw (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
In his work, Manuel Atienza considers the legal argument essential to legitimise decisions in a democratic society, avoiding both authoritarian formalism and the dissolution of law in morality. A key area of application is bioethics, where issues such as end of life and access to care involve fundamental values. Atienza criticises the rigidly legalistic approach, the moral prejudices and the political exploitation that complicate the debate more than the nature of the problems themselves. Instead he proposes bioethics as an argumentative dialogue, based on rational discussion and the collective construction of shared solutions. From this perspective, human dignity emerges as the founding principle of rights, guiding legal and ethical choices towards solutions that respect the plurality of values. This contribution explores his theory with particular attention to the role of dignity in legal and ethical discourse.
Keywords: Atienza; bioethics; biolaw; dignity; argumentation